PERAN ORGANISASI KEMASYARAKATAN PEMUDA (OKP) OPHILBAS DALAM PROGRAM UMKM DI KELURAHAN BATANG KABUNG GANTING KOTA PADANG - muhammad raziq rousan fikri; Adil Mubarak (Jurusan Ilmu Administrasi Negara, 2024)
Youth is synonymous with the icon as the 'driving force of the nation.' This is not without reason since the proclamation of the Indonesian nation on August 17, 1945. The younger generation has dominated much of the history of struggle against colonialism that sought to control Indonesia, especially through youth organizations. In this study, the author uses a descriptive approach used to convey in detail the secondary and primary data obtained related to the Role of Youth Community Organizations (OKP) ophilbas in the Micro, Small, and Medium Enterprises (MSME) program in the Batang Kabung Ganting Subdistrict of Padang City. The data obtained will be analyzed using the triangulation source technique. The identification of the Role and inhibiting factors of OKP ophilbas in MSMEs in the Batang Kabung Ganting Subdistrict of Padang City through education and training, economic development and OKP funds, awareness, and participation in utilizing existing potential for further development is through training, skills, and increasing insights organized by several related parties. In the business implementation, the capital holders are entitled to use the funds for entrepreneurial purposes. The assistance provided is only monitoring the allocation of funds, encouragement, and motivation for young people. The inhibiting factors of the role of OKP ophilbas in the MSME program are the suboptimal role of OKP, unsuccessful programs, lack of funding, lack of awareness in participation, and weather factors.